Особливості застосування листової термоміграції трирозмірної рідкої зони Al+Si для формування напівпровідникових силових приладів - Polukhin, Оlекsіі; Kravchina, Vitalii (PE "Politekhperiodika", Book and Journal Publishers, 2023)
The paper considers using the technology of sheet thermomigration of three-dimensional zones, which implements p+-Si* liquid epitaxy on an n-Si wafer, to produce power semiconductor devices with crystals having thinned layers of high-resistive n-Si base, which are surrounded by p+-Si* side insulation regions, and thickened p+-Si* emitter layers. This technology, which has a number of advantages, was used to create diode arrays in n-Si with a specific resistance of 20 Ω·cm. For recrystallization, p+-Si* wafers with a resistivity of 0.005 Ω·cm were used. The produced direct polarity diodes had a breakdown voltage of 1000 V, a forward voltage drop of 1.17 V at a current density of 2.0 A/mm2, and a reverse resistance recovery time of trr = 1.5 μs. Additional use of the technology of creation of recombination centers allowed to further improve trr to 0.5 μs.